2006
DOI: 10.1007/s00248-006-9155-4
|View full text |Cite
|
Sign up to set email alerts
|

Ciliates are the Dominant Grazers on Pico- and Nanoplankton in a Shallow, Naturally Highly Eutrophic Lake

Abstract: Abundance and biomass of the microbial loop members [bacteria, heterotrophic nanoflagellates (HNF), and ciliates] were seasonally measured in the naturally eutrophic and shallow (2.8 mean depth) Lake Võrtsjärv, which has a large open surface area (average 270 km2) and highly turbid water (Secchi depth <1 m). Grazing rates (filter feeding rates) on 0.5-, 3-, and 6-microm-diameter particles were measured to estimate pico- and nanoplankton grazing (filter feeding) by micro- and metazooplankton. Among grazers, HNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 43 publications
5
52
0
1
Order By: Relevance
“…found that, unlike several other eutrophic and shallow lakes, the contribution of macrophytes to the Lake Võ rtsjä rv C budget was low (only 5%). Carbon biomass estimates from Zingel et al (2007) showed that filamentous phytoplankton and bacteria were the most important reservoirs of the living carbon biomass in Võ rtsjä rv. Against our expectations, d 13 C signatures of Au-DOM in Võ rtsjä rv were lower than those of the allochthonous riverine DOM.…”
Section: Discussionmentioning
confidence: 99%
“…found that, unlike several other eutrophic and shallow lakes, the contribution of macrophytes to the Lake Võ rtsjä rv C budget was low (only 5%). Carbon biomass estimates from Zingel et al (2007) showed that filamentous phytoplankton and bacteria were the most important reservoirs of the living carbon biomass in Võ rtsjä rv. Against our expectations, d 13 C signatures of Au-DOM in Võ rtsjä rv were lower than those of the allochthonous riverine DOM.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may generalize to an almost cosmopolitan distribution throughout these aquatic systems (Pfister et al, 2002). Several of the observed morphotypes, such Uronema, Cyclidium, Rimostrombidium (Šimek et al, 1995;Zingel et al, 2007), Mesodinium, Colpoda (Foissner et al, 1999;Zingel and Nõges, 2010), and Halteria (Šimek et al, 1995), graze on picoplankton, these may include nanociliates which play an important role in energy and matter transfer through the microbial web because of the high metabolic rates associated with their small size.…”
Section: Ciliate Assemblage Compositionmentioning
confidence: 78%
“…Physical interference by trichomes has been proposed as a mechanism that reduces ciliate predation, and it is an important process because top-down control by predatory fish likely has a strong effect on the microbial web of tropical lakes (Havens et al, 2007). Zingel et al (2007) determined that ciliates are the dominant microbial grazers at a temperate lake that is also dominated by filamentous cyanobacteria because top-down control by fish predators did not occur under these conditions. The dominant cyanobacteria at Catemaco produce toxins (Berry and Lind, 2010) that have unknown effects on other components of the microbial web, and the effect of these toxins on the ciliate assemblages is also unknown.…”
Section: Ciliate Assemblage Compositionmentioning
confidence: 99%
See 2 more Smart Citations